2015
DOI: 10.1017/s0950268815001454
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological dynamics of nephropathia epidemica in the Republic of Tatarstan, Russia, during the period of 1997–2013

Abstract: This report summarizes epidemiological data on nephropathia epidemica (NE) in the Republic of Tatarstan, Russia. NE cases identified in the period 1997-2013 were investigated in parallel with the hantavirus antigen prevalence in small rodents in the study area. A total of 13 930 NE cases were documented in all but one district of Tatarstan, with most cases located in the central and southeastern districts. The NE annual incidence rate exhibited a cyclical pattern, with the highest numbers of cases being regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…NE is endemic in the Republic of Tatarstan where the highest annual prevalence of 64.4 cases per 100,000 was registered in 1997 [5]. Clinically, NE is characterized by an acute onset of high fever, headache, and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…NE is endemic in the Republic of Tatarstan where the highest annual prevalence of 64.4 cases per 100,000 was registered in 1997 [5]. Clinically, NE is characterized by an acute onset of high fever, headache, and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…CD4+, CD8+ and CD20+ lymphocyte infiltration was detected in kidney tissue (Figure 5D, E and F). Also, clusterin expression (which has been previously associated with HFRS) [1,18] was demonstrated at the basal side of the tubular epithelial cells (Figure 5G). Immunofluorescent analysis revealed that infiltrating leukocytes were CD4+, CD8+ and CD20+, suggesting that lymphocytes (T-helpers, cytotoxic T cells (CTL) and B cells) are primarily migrating across the endothelium.…”
Section: Resultsmentioning
confidence: 70%
“…Hemorrhagic fever with renal syndrome (HFRS) is an acute zoonotic disease endemic in the Republic of Tatarstan, Russia [1]. Puumala orthohantavirus (PUUV) is commonly isolated from human HFRS blood and tissue samples as well as bank voles captured in the region [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most active fractions of highly purified antigens were used to immunize clinically healthy sheep by sequential 4-fold administration of inactivated antigen at intervals of 14 days in a mixture with Incomplete Freund's Adjuvant (Thermo Fisher Scientific) intramuscularly into the medial thigh area in a volume of 16 cm 3 . The blood sampling was made from the vascular vein when the serum titers reached 1:6400-1:12800 in ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Domestic and wild animals participate in the spread of rabies, as well as other zoonotic infections. [3,4] As a lethal anthropozoonotic infection, rabies causes significant economic damage, resulting from the costs of specific prevention among wild and farm animals [5] and diagnostic tests. Therefore, to increase the effectiveness of antiepizootic measures, it is necessary not only to conduct extensive monitoring studies [6] but also to improve methods for diagnosing rabies, [7,8] in particular, ELISA-based test systems using highly purified specific components -antigens and globulins.…”
Section: Introductionmentioning
confidence: 99%